Apoyo en secretaria de Infraestructura en el Municipio de Duitama en revisión de proyectos civiles como auxiliar en ingeniería civil - Gómez López, Cristian David (Universidad Antonio Nariño, 2022)
This work is presented as a degree work, its research is mixed, since, it has a qualitative and quantitative methodology, It is based on the internship modality in the Faculty of Civil Engineering at the Antonio Nariño Univer sity, Duitama Headquarters, which will aim to support the Secretariat of Infrastructure of the Municipality of Duitama as a civil engineering assistant, for the development of activities such as: preparation of road diagnostic reports, budget management, c alculation of quantities, accompaniment in road maintenance Works on flexible pavements, Longitudinal measurements of the road network along with its location through the GOOGLE EARTH software assigned by the Secretariat of Infrastructure, review of projec ts by infrastructure, and those mentioned in the activities log, accompanied by their photographic record evidencing the activities carried out during my internship.